2011
DOI: 10.1002/iub.479
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles for targeted vascular delivery

Abstract: Magnetic targeting has shown promise to improve the efficacy and safety of different classes of therapeutic agents by enabling their active guidance to the site of disease and minimizing dissemination to nontarget tissues. However, its translation into clinic has proven difficult because of inherent limitations of traditional approaches inapplicable for deep tissue targeting in human subjects and a need for developing well-characterized and fully biocompatible magnetic carrier formulations. A novel magnetic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Dividing cells were shown to process MNPs many times faster than contact-inhibited cells, possibly as a result of the rapid cumulative expansion of the cytosol compartment promoting solubilization of the released oligomeric fragments and facilitating their diffusion from the particle matrix. Thus, in the therapeutic context of magnetically targeted drug or cell delivery as a therapeutic strategy for preventing arterial restenosis (35), our experiments offer several important observations. The increased rates of MNP disassembly in an acidified semisolid environment and in dividing smooth muscle cells suggest that the degradation of the respective fractions of the arterial wall-localized MNPs, i.e., those immobilized in the extracellular matrix or taken up by neointimal cells, may occur substantially faster early in the healing phase, characterized by rapid cell proliferation and inflammation, which may cause acidification of the local microenvironment (36).…”
Section: Discussionmentioning
confidence: 88%
“…Dividing cells were shown to process MNPs many times faster than contact-inhibited cells, possibly as a result of the rapid cumulative expansion of the cytosol compartment promoting solubilization of the released oligomeric fragments and facilitating their diffusion from the particle matrix. Thus, in the therapeutic context of magnetically targeted drug or cell delivery as a therapeutic strategy for preventing arterial restenosis (35), our experiments offer several important observations. The increased rates of MNP disassembly in an acidified semisolid environment and in dividing smooth muscle cells suggest that the degradation of the respective fractions of the arterial wall-localized MNPs, i.e., those immobilized in the extracellular matrix or taken up by neointimal cells, may occur substantially faster early in the healing phase, characterized by rapid cell proliferation and inflammation, which may cause acidification of the local microenvironment (36).…”
Section: Discussionmentioning
confidence: 88%
“…Magnetic targeting is based on two primary elements: a magnetic field source and a magnetically responsive drug carrier [111]. …”
Section: External Stimuli-triggered Deliverymentioning
confidence: 99%
“…Now, the MNPs have been widely applied to biological and medical areas [3][4][5], such as drug and gene delivery [6,7], the control of cells and cellular function [8,9], therapeutic hyperthermia [10,11], bioseparation [12,13], magnetic resonance imaging [14][15][16][17], and quantitative immunoassay [18,19]. Beyond the biomedical area, interesting studies have been reported on the use of MNPs for ferrofluids, data storage, and catalysis [20].…”
Section: Introductionmentioning
confidence: 99%